LncRNA SLC16A1-AS1 Suppresses Cell Proliferation in Cervical Squamous Cell Carcinoma (CSCC) Through the miR-194/SOCS2 Axis - Zhang H; Jin S; Ji A; Ma Y; Zhang C; Wang A; Wang R (Cancer Management and Research, 2021)
Huizhen Zhang,1 Shuangling Jin,1 Aifang Ji,2 Ying Ma,3 Chunyan Zhang,1 Ailan Wang,1 Rui Wang1 1Department of Gynecology, Heping Hospital Affiliated to Changzhi Medical College, Changzi, Shanxi Province, 046000, People’s Republic of China; 2Department of Clinical Laboratory, Heping Hospital Affiliated to Changzhi Medical College, Changzi, Shanxi Province, 046000, People’s Republic of China; 3Department of Obstetrics, Heping Hospital Affiliated to Changzhi Medical College, Changzi, Shanxi Province, 046000, People’s Republic of ChinaCorrespondence: Shuangling JinDepartment of Gynecology, Heping Hospital Affiliated to Changzhi Medical College, Changzhi City, Shanxi Province, 046000, People’s Republic of ChinaEmail nj6077@163.comBackground: SLC16A1-AS1 has been characterized as an oncogenic long non-coding (lncRNA) in breast cancer and bladder cancer, while its role in cervical squamous cell carcinoma (CSCC) is unknown.Methods: CSCC and non-tumor tissue samples were collected from 60 female patients, and qPCR was performed to detect the expression of SLC16A1-AS1, miR-194 and SOCS2. Luciferase reporter assay was performed to detect the interaction between SLC16A1-AS1 and miR-194. Colony formation assay was used to detect cell proliferation.Results: SLC16A1-AS1 was down-regulated in CSCC and correlated with poor survival. Overexpression of SLC16A1-AS1 could inhibit the proliferation of cervical cancer cells. In addition, SLC16A1-AS1 could sponge miR-194 and increase the expression levels of SOCS2, ultimately inhibiting the proliferation of cervical cancer cells.Conclusion: SLC16A1-AS1 was downregulated in CSCC and suppressed cell proliferation in cervical squamous cell carcinoma (CSCC) through the miR-194/SOCS2 axis.Keywords: cervical squamous cell carcinoma, SLC16A1-AS1, miR-194, SOCS2